How to build a time machine : the real science of time travel - Clegg, Brian (New York : St. Martin's, 2011)
"In How to Build a Time Machine, Brian Clegg provides an understanding of what time is and how it can be manipulated. He explores the remarkable possibilities of real time travel that emerge from quantum entanglement, superluminal speeds, neutron star cylinders and wormholes in space. With the fascinating paradoxes of time travel echoing in our minds will we realize that travel into the future might never be possible? Or will we realize there is no limit on what can be achieved, and take on this ultimate challenge? Only time will tell"-- Provided by publisher.
A glittering metal framework -- It's all relative -- Time past -- Time's arrow -- The time travellers' convention -- Back to the future -- Warp factor four -- Entangled web -- Phantoms of time -- Interstellar engineering -- Alice through the wormhole -- The Mallett Machine -- Killing grandfather -- Fact or fiction?
Includes bibliographical references (p. 277-290) and index.
Keywords: Time travel; Space and time